دور الهيكل التنظيمي كأحد متطلبات التغيير التنظيمي في علاج الفساد الإداري في وحدات الحكم المحلي بمحافظة السويس - محمد، رضا عبدالفتاح إبراهيم (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2018)
هدفت الدراسة إلى معرفة دور الهيكل التنظيم في الحد من الفساد الإداري في وحدات لحكم المحلي بمحافظة السويس، وقد استخدمت الباحثة المنهج الوصفي التحليلي لهذا الغرض، واستخدمت قائمة الاستقصاء كأداة رئيسية لجمع البيانات، وبلغ حجم المجتمع (1497)، فيما بلغت عينة الدراسة (306) مفردة، كما تم استخدام برنامج التحليل الإحصائي (SPSS) كرزمة إحصائية متكاملة لإدخال ومعالجة البيانات واختبار الفرض، وتوصلت نتائج الدارسة إلى أنه توجد علاقة ذات دلالة إحصائية بين التغيير في الهيكل التنظيمي وعلاج الفساد الإداري في وحدات الحكم المحلي بمحافظة السويس، كما أوصت الباحثة بضرورة الاهتمام بالهيكل التنظيمي لأي مؤسسة لأنه الأداة الهادفة لمساعدتها على تحقيق أهدافها بكفاءة وفاعلية، وذلك من خلال المساعدة في تنفيذ الخطط واتخاذ القرارات وتحديد أدوار الأفراد وتحقيق الانسجام بين مختلف الوحدات بالمؤسسة.
The study aimed to know the role of organizational structure in reducing administrative corruption in local government units in Suez Governorate, The researcher used the analytical descriptive method for this purpose, and used the survey list as its main tool for data collection, The total size of the community (1497), while the sample of the study (306) single The Statistical Analysis Program (SPSS) was also used as an integrated statistical package for data entry, processing and hypothesis testing, The results of the study showed that there is a statistically significant relationship between the change in the organizational structure and the treatment of administrative corruption in the local government units in Suez Governorate, The researcher also recommended the need to pay attention to the organizational structure of any institution because it is the tool aimed at helping them achieve their goals efficiently and effectively By assisting in the implementation of plans and decisions, and determining the roles of individuals and achieve harmony between the various units in the institution.
Keywords: الإدارة المحلية -- الهيكل التنظيمي -- التغيير التنظيمي -- الفساد الإداري -- محافظة السويس -- مصر